Advances in Chinese and Western Diagnosis and Treatment of Bertolotti Syndrome - Tang, Mei; Wu, Wenyi; Chen, Jianfeng (Journal of Contemporary Medical Practice, 2025)
Bertolotti syndrome (BS), also known as fifth lumbar transverse process hypertrophy syndrome, is a clinical syndrome characterized by lumbosacral translocated vertebrae (LSTV), and is a relatively rare but easily overlooked chronic lower back pain condition. As a relatively rare but easily overlooked structural disorder, BS has long been categorized as "nonspecific lower back pain" in clinical practice. Nowadays, people's attention to lumbosacral migratory vertebrae causing low back pain has been increased, and the diagnosis and treatment of BS have been reported to be increasing in the international literature year by year. Through reviewing the relevant literature at home and abroad in recent years, the author found that Western medicine has made more in-depth research on the imaging and surgical interventions of BS, but lacks breakthrough treatments for the recurring lumbar pain, whereas traditional Chinese medicine has achieved certain clinical efficacy through the combination of traditional Chinese medicine, acupuncture, and massage. Traditional Chinese medicine (TCM) has achieved certain clinical efficacy through a combination of traditional Chinese medicine, acupuncture, tuina and other means, but more research is needed on the material basis and mechanism of its effect. However, more research is needed on the material basis of its effect and its mechanism of action. The combination of Chinese and Western medicine shows unique advantages in precise localization of lesions and improvement of pain and function, which is worthy of further in-depth study. In this paper, we review the Chinese and Western medicine diagnosis and treatment of BS, aiming to provide new ideas and methods for the diagnosis and treatment of BS.